Charles Darwin and the Theory of Natural Selection - Skelton, Renee; Robinson, Jim (New York : Barron's, 1987)
Traces the life of the English naturalist from his early years through his expedition aboard the H.M.S. Beagle and the development of his theory of evolution by natural selection.
Includes index.
Bibliography: p. 116.
Keywords: Darwin, Charles, -- 1809-1882 -- Juvenile literature; Darwin, Charles, -- 1809-1882; Natural selection -- Juvenile literature; Evolution (Biology) -- Juvenile literature; Naturalists -- Biography -- England; Naturalists; Evolution; Natural selection